The Impact of PhET-Assisted Problem-Solving Model on Enhancing Students' Physics Problem-Solving Skills in Indonesian High Schools - Harudu, La; Nursalam, La Ode; Kasmiati, Sitti; Hasan, Sakka; Sugiarto, Agus; Karim, Ahmad Tarmizi Abdul; Syarifuddin, S.; Sejati, Andri Estining (LITPAM, 2024)
This study investigates the impact of a PhET-assisted problem-solving model on high school students' physics problem-solving skills, especially in resource-limited educational settings in Indonesia. Conducted as a quasi-experimental study with a non-equivalent control group pretest-posttest design, the research involved 50 students from SMAN 10 Kendari, divided into an experimental group receiving instruction through the PhET-assisted model and a control group following traditional teaching methods. The intervention consisted of structured learning sessions incorporating PhET simulations, designed to engage students actively with physics concepts through virtual experiments. Data were collected using a 10-item problem-solving test and analyzed using a one-way ANOVA to determine the statistical significance of differences in performance between groups. Results revealed a significant improvement in the experimental group, with a mean increase of 47.91 points from pretest to posttest (M = 83.54, SD = 15.22) compared to the control group’s improvement of 39.11 points (M = 74.48, SD = 12.78). The ANOVA results (F = 23.526, p < 0.001) confirm that the PhET-assisted model significantly enhanced students' problem-solving skills. These findings suggest that PhET simulations can be an effective tool for improving physics learning outcomes in schools with limited access to laboratory resources. Integrating PhET simulations into the physics curriculum could provide students with accessible, interactive learning experiences that bridge the gap in traditional laboratory access, fostering a deeper understanding and application of physics concepts.